A review on multicomponent reactions catalysed by zero-dimensional/one-dimensional titanium dioxide (TiO2) nanomaterials: Promising green methodologies in organic chemistry. (1st February 2021) - Govardhana Reddy, Peddiahgari Vasu; Rajendra Prasad Reddy, Bhoomireddy; Venkata Krishna Reddy, Motakatla; Raghava Reddy, Kakarla; Shetti, Nagaraj P.; Saleh, Tawfik A.; Aminabhavi, Tejraj M.
Abstract: Heterogeneous catalysis has currently become an emerging tool for the design and development of sustainable manufacturing processes in order to obtain advanced intermediates, fine chemicals, and bioactive molecules. This field has been considered efficient and eco-friendly, as it investigates the utilization of non-hazardous metals for atom-economical reactions. Nanomaterials have created a significant impact on scientific and engineering advancements due to their tunable properties with superior performance over their massive counterparts. Due to the increased demand for heterogeneous catalysts in industries and academia, different transition metal oxides have been made into substantial nanostructures. Among them, titanium dioxide (TiO2 ) nanomaterials have received more attention on account of their chemical stability, low cost, dual acid-base properties, good oxidation rate and refractive index. Different modifications of TiO2 extend their applications as active catalysts or catalyst supports in diverse catalytic processes, such as photovoltaics, lithium batteries, pigments and others. One-dimensional (1-D) TiO2 nanostructures such as nanotubes, nanowires and nanorods have achieved greater importance owing to the unique properties of improved porosity, decreased inter-crystalline contacts, large surface-to-volume ratio, superior dispersibility, amplified accessibility of hydroxyl (-OH) groups and presence of good concentrations of Brønsted/Lewis acid sites. Since the discovery, 1-D TiO2 nanostructures have served good photocatalytic applications, but were less explored in organic transformations. While many articles and reviews have covered the applications of 0-D and 1-D TiO2 nanostructured materials (NSMs) in photoelectrochemical reactions and solar cells, there are other interesting applications of these as well. In contrast to the conventional multi-step processes that utilise the stepwise formation of individual bonds, one-pot conversions based on multicomponent reactions (MCRs) have acquired much significance in contemporary organic synthesis. This paper presents a critical review on history, classification, design and synthetic utility of titania-based nanostructures, which could be used as robust solid-acid catalysts and catalyst supports for MCRs. Further, to put ideas into perspective, the introduction and applications of MCRs for various organic transformations have been discussed. Graphical abstract: Image 1 Highlights: We demonstrated that the titania nanostructures can be used as highly efficient catalysts towards multi-component reactions. 1-D TiO2 nanostructures have extremely served for photocatalytic applications, but less explored in organic transformations. The high efficiency and reusability of the catalysts is mainly attributed to plenty of Lewis and Brønsted acid sites available on the nanotubular catalyst surface. This green protocol suggests various advantages like requirement of less catalyst loading, high reaction rates, operational simplicity and mild reaction conditions.